Analisa Barrier Implementasi Sistem Pada Website Sistem Informasi Kesehatan Terpadu (SIKAT) di Puskesmas Kutabumi - Lulasnov Viola Prameswari Ken Putri; Irwan Susanto; Darmansah Darmansah (STMIK Budi Darma, 2022)
The health information system (SIK) is a systematic and integrated health data and information system at the government level in fulfilling health management support to improve services to the community. The Kutabumi Health Center has an Integrated Health Information System (SIKAT) which is directly integrated with the Health Office. The Integrated Health Information System (SIKAT) is available in the form of a website which is an information system website to assist the process of running health services at the Kutabumi Health Center, one of which is data entry. This study aims to determine the problems that occur at the Kutabumi Health Center related to the implementation of an integrated health information system (SIKAT) related to phenomena that have been proven. Based on this, it is necessary to analyze the system implementation barriers which are expected to provide an overview of the existing system management conditions and provide recommendations to produce information from an appropriate system, in order to achieve the goals set by the Kutabumi Health Center. This research method uses an analytical approach to technology/innovation implementation barriers with dimensions of organizational inertia, habitual routines, and poor readiness (financial & human resources). The analysis in this study uses chi square and contingency analysis. The results showed that the factors of unfavorable readiness (financial factor readiness), routine habits (habits), organizational slack (description of organizational structure and leadership mandate) were the inhibiting factors for the implementation of SIKAT at the Kutabumi Health Center.